Answer:
see explanation
Explanation:
Given
![(6(2a-4c)-6(6a-4b)+3(4b-8c))/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/309hl0e2peirh3pv6f9ml0nt9ldktzhnrv.png)
Distribute the 3 parenthesis on the numerator
=
![(12a-24c-36a+24b+12b-24c)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4254j32sk1bpchoagxpknh692s2fgcxs2s.png)
Collect like terms on the numerator
=
![(-24a+36b-48c)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5we22og45etdb4u21s4n5m5h6w5grrzqyq.png)
Divide each of the terms on the numerator by 4
=
+
+
![(-48c)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yj0y2ujrr930pyeeh2g5tuibii69h60qk2.png)
= - 6a + 9b - 12c ← factor out - 3 from each term
= - 3(2a - 3b + 4c)
Compare with
X(2a + Bb + Cc) to obtain
X = - 3, B = - 3, C = 4